The influence of imagery vividness on cognitive and perceptual cues in circular auditorily-induced vection - Väljamäe, Aleksander; Sell, Sara (Frontiers in Psychology, 2014)
In the absence of other congruent multisensory motion cues, sound contribution to illusions of self-motion (vection) is relatively weak and often attributed to purely cognitive, top-down processes. The present study addressed the influence of cognitive and perceptual factors in the experience of circular, yaw auditorily-induced vection (AIV), focusing on participants’ imagery vividness scores. We used different rotating sound sources (acoustic landmark vs. movable types) and their filtered versions that provided different binaural cues (interaural time or level differences, ITD vs. ILD) when delivering via loudspeaker array. The significant differences in circular vection intensity showed that 1) AIV was stronger for rotating sound fields containing auditory landmarks as compared to movable sound objects; 2) ITD based acoustic cues were more instrumental than ILD based ones for horizontal AIV; and 3) individual differences in imagery vividness significantly influenced the effects of contextual and perceptual cues. While participants with high scores of kinesthetic and visual imagery were helped by vection ``rich" cues, i.e. acoustic landmarks and ITD cues, the participants from the low-vivid imagery group did not benefit from these cues automatically. Only when specifically asked to use their imagination intentionally did these external cues start influencing vection sensation in similar way to high-vivid imagers. These findings are in line with the recent fMRI work which suggested that high-vivid imagers employ automatic, almost unconscious mechanisms in imagery generation, while low-vivid imagers rely on more schematic and conscious framework. Consequently, our results provide an additional insight into the interaction between perceptual and contextual cues when experiencing purely auditorily or multisensorily induced vection.